The Influence of Vitamin D Receptor Gene Polymorphisms in Spondyloarthritis - Janisleya Silva Ferreira Neves; Jeane Eliete Laguila Visentainer; Denise Manjurma da Silva Reis; Marco Antonio Rocha Loures; Hugo Vicentin Alves; Fernanda Formaggi Lara-Armi; Josiane Bazzo de Alencar; Joana Maira Valentin Zacarias; Ana Maria Sell (International Journal of Inflammation)
Spondyloarthritis (SpA) is an inflammatory rheumatic disease related to low bone mineral density. Because vitamin D plays an important role in bone metabolism and immune system modulation, the aim of this study was to evaluate the influence of polymorphisms in vitamin D receptor genes (VDR) in the development of SpA. In this case–control study, a total of 244 patients with SpA and 197 individuals with no SpA were included. Among the patients, 174 had ankylosing spondylitis (AS) and 66 had psoriatic arthritis (PsA). Genotyping of FokI (rs2228570 C > T), BsmI (rs1544410 C > T), ApaI (rs7975232 A > C), and TaqI (rs731236 T > C) was performed using PCR-RFLP, while genotyping of HLA-B∗27 was performed using PCR-SSP. Serum levels for hydroxy (OH) vitamin D and the clinical activity index of the disease (BASDAI) were also evaluated. SNPStats and OpenEpi software were used for statistical analysis. The ApaI a allele and ApaI a/a genotype were less frequent in PsA compared with controls. The ApaI a/a genotype was associated with a protecting factor for PsA in females, and ApaI A/a was associated with a protecting factor for the disease in HLA-B∗27 positive patients. Notwithstanding, the ApaI a/a genotype was a risk factor for SpA and AS in males. The FokI f/f genotype was associated with a better clinical activity in PsA. When considering the covariates, vitamin D sufficiency, and gender, the FokI F/F genotype was associated with a risk factor in males with SpA and AS compared with females with this same genotype. In conclusion, the ApaI rs7975232 polymorphism was associated with PsA, and the FokI rs2228570 polymorphism was associated with better clinical PsA activity. ApaI and FokI were associated with SpA and AS when considering gender and vitamin D sufficiency.